Maternal organic selenium supplementation during gestation improves the antioxidant capacity and reduces the inflammation level in the intestine of offspring through the NF-κB and ERK/Beclin-1 pathways. Issue 1 (10th December 2020) - Mou, Daolin; Ding, Dajiang; Yang, Min; Jiang, Xuemei; Zhao, Lianpeng; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Lin, Yan; Zhuo, Yong; Li, Jian; Huang, Chao; et al.
Abstract : Maternal HMSeBA supplementation during gestation improves offspring's intestinal antioxidant capacity and reduces the intestinal inflammation level by suppressing NF-κB and ERK/Beclin-1 signaling. Abstract : Selenium (Se) is postulated to protect against inflammation in the gut by attenuating oxidative stress. This study was conducted to investigate the effects of maternal 2-hydroxy-4-methylselenobutanoic acid (HMSeBA), an organic Se source, on the intestinal antioxidant capacity and inflammation level of the offspring and its possible mechanism. Forty-three sows were randomly assigned to receive one of the following three diets during gestation: control diet, sodium selenite (Na2 SeO3 ) supplemented diet or HMSeBA supplemented diet, respectively. Samples were collected from the offspring at birth and weaning. The results showed that maternal HMSeBA supplementation significantly upregulated ileal GPX2 and SePP1 gene expression compared with the control and Na2 SeO3 groups, while suppressed the expression of ileal IL-1β, IL-6 and NF-κB genes in newborn piglets compared with the control group. Moreover, maternal HMSeBA supplementation significantly increased the protein of ileal GPX2 and p-mTOR compared with the control and Na2 SeO3 groups, but decreased the ileal p-NF-κB, Beclin-1 and p-ERK proteins in newborn piglets compared with the control group. The weaned piglets of the HMSeBA group had lower serum IL-1β and IL-6 than the piglets of the control group at 2 h of LPS challenge. In addition, after the LPS challenge, the HMSeBA group had a lower relative abundance of ileal p-NF-κB and Beclin-1 proteins than the control and Na2 SeO3 groups. In conclusion, maternal HMSeBA supplementation during gestation can improve the offspring's intestinal antioxidant capacity and reduce the inflammation level by suppressing NF-κB and ERK/Beclin-1 signaling.